Effects of Isotretinoin on Serum Vitamin-D Levels among Severe Acne Vulgaris patients - Mohammad Asif, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Medical issue that causes inflammation of skin resulting in psychological and social distress is acne vulgaris. Vitamin D plays a critical role in its pathology due to its immune-modulatory effects. Aim: To evaluate the effects of isotretinoin on vitamin D levels among severe acne vulgaris patients. Study design: This was quasi experimental trial. Methodology: This experiment at the Lahore General Hospital involved 100 participants with severe acne vulgaris. Iso-tretinoin in a dose of 0.75 mg/kg was given daily for 4 months. Serum Serum vitamin-D levels were considered at two points: before and after treatment. The data was entered and analyzed in SPSS 25. A paired sample t-test was used to compare the mean Vitamin-D levels before and after treatment in acne vulgaris patients. A p-value ≤ 0.05 was considered significant. Results: The mean age of the patients was 28.5±6.2 years. There was significant difference in mean Vitamin D serum levels before and after treatment in acne vulgaris patients. Practical Implication: Acne vulgaris is a major problem in modern era. This investigation will highlight the role of oral iso-tretinoin on vitamin D levels among severe acne local patients. Due to lack of local literature, this study will add information to existing literature. Conclusion: It was concluded that isotretinoin treatment increased 25 OH vitamin D levels in patients suffering from severe AV. Although acne vulgaris impacts negatively to vitamin-D levels. Keywords: Acne Vulgaris, Isotretinoin, Effectiveness and Treatment Outcomes.